2020
DOI: 10.3390/app10175824
|View full text |Cite
|
Sign up to set email alerts
|

Working Length Transfer in the Endodontic Clinical Practice: A Comparative Study

Abstract: The present paper evaluated the accuracy of two different methods for transferring working length (WL) between manual endodontic instruments and nickel–titanium (NiTi) shaping files. Thirty root canals of extracted permanent teeth were used. Root canals were divided according to canal length (CL) and canal curvature (CC). The reference cusp and the root end were flattened to provide reproducible and accurate measurements. During shaping, the WL measurements were obtained with manual k-files (KF) and transferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Changes in canal curvature (angle and radius) after the use of the two different NiTi single file systems were statistically significant. This agrees with the findings of previous studies which found that both motions (continuous rotation, reciprocating motion) make a significant difference in the original shape of the curved root canal [ 22 , 25 ]. The reason for these changes may be the high range of curvature of the selected root canals, which are often narrow canals, and the large taper sizes of both single file Reciproc blue and One Curve.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Changes in canal curvature (angle and radius) after the use of the two different NiTi single file systems were statistically significant. This agrees with the findings of previous studies which found that both motions (continuous rotation, reciprocating motion) make a significant difference in the original shape of the curved root canal [ 22 , 25 ]. The reason for these changes may be the high range of curvature of the selected root canals, which are often narrow canals, and the large taper sizes of both single file Reciproc blue and One Curve.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that evaluation of the changes on canal shape elements such as curvature and working length after instrumentation is a reliable process to assess the ability of rotary system to preserve the original shape of curved root canal [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have approached various aspects regarding the behavior of endodontic instruments, including the influence of lubricants on torsional loads [27], metallurgical features [28], comparison between manual instruments and NiTi files [29], influence of heat sterilization procedures [30] or of surface design [31]. During root canal preparation, endodontic instruments are exposed to torsional and flexural stresses, the former for straight root canals and the latter for curved ones [32].…”
Section: Discussionmentioning
confidence: 99%